Accelerating in vivo fast spin echo high angular resolution diffusion imaging with an isotropic resolution in mice through compressed sensing. Issue 3 (3rd October 2020) - Naeyaert, Maarten; Aelterman, Jan; Van Audekerke, Johan; Golkov, Vladimir; Cremers, Daniel; Pižurica, Aleksandra; Sijbers, Jan; Verhoye, Marleen
Abstract : Purpose: Echo planar imaging (EPI) is commonly used to acquire the many volumes needed for high angular resolution diffusion Imaging (HARDI), posing a higher risk for artifacts, such as distortion and deformation. An alternative to EPI is fast spin echo (FSE) imaging, which has fewer artifacts but is inherently slower. The aim is to accelerate FSE such that a HARDI data set can be acquired in a time comparable to EPI using compressed sensing. Methods: Compressed sensing was applied in either q‐space or simultaneously in k‐space and q‐space, by undersampling the k‐space in the phase‐encoding direction or retrospectively eliminating diffusion directions for different degrees of undersampling. To test the replicability of the acquisition and reconstruction, brain data were acquired from six mice, and a numerical phantom experiment was performed. All HARDI data were analyzed individually using constrained spherical deconvolution, and the apparent fiber density and complexity metric were evaluated, together with whole‐brain tractography. Results: The apparent fiber density and complexity metric showed relatively minor differences when only q‐space undersampling was used, but deteriorate when k‐space undersampling was applied. Likewise, the tract density weighted image showed good results when only q‐space undersampling was applied using 15 directions or more, but information was lost when fewer volumes or k‐space undersampling were used. Conclusion: It was found that acquiring 15 to 20 diffusion directions with a full k‐space and reconstructed using compressed sensing could suffice for a replicable measurement of quantitative measures in mice, where areas near the sinuses and ear cavities are untainted by signal loss.